2016
DOI: 10.18679/cn11-6030/r.2016.011
|View full text |Cite
|
Sign up to set email alerts
|

Dementia in Taiwan area

Abstract: KEYWORDSAlzheimer's disease; ascertainment of dementia 8 (AD8); acetyl-cholinesterase inhibitor; dementia Objective: Taiwan has an increasing aging population like other developed areas. The aging population will lead to an increased prevalence of dementia. Methods: This article will reflect the status of dementia in Taiwan, including updated epidemiology, diagnosis, subtypes, and optimal treatment of dementia. Results: The article also describes and interprets the Taiwan Dementia Policy to establish a clear, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 19 publications
1
3
0
Order By: Relevance
“…We have also reported the rule of treatment of AD in Taiwan elsewhere. 14 In our study, we found a higher risk of UI in patients with AD than in the general population. However, the pathophysiological mechanism for UI in AD has not been well known but is presumed to be multifactorial.…”
Section: Discussionsupporting
confidence: 51%
“…We have also reported the rule of treatment of AD in Taiwan elsewhere. 14 In our study, we found a higher risk of UI in patients with AD than in the general population. However, the pathophysiological mechanism for UI in AD has not been well known but is presumed to be multifactorial.…”
Section: Discussionsupporting
confidence: 51%
“…Cognitive decline was defined as patient self-reported cognitive impairment with a decline of MMSE ≥ 2 points from baseline. The cutoff points were based on the regulation of the Taiwan National Health Insurance Administration [ 33 ]. Previous literature showed that the average intermediate progression rate is usually in the range of 2.0–4.9 points per year for AD [ 34 ] and 2.1–2.5 points per year for PD [ 35 ].…”
Section: Methodsmentioning
confidence: 99%
“…Some of the reasons for under-diagnosis and low utilization of long-term care services might be due to public stigma related to dementia, underreport by patients and families, and families’ unawareness of services. Most families might treat memory or cognitive decline as a part of normal aging process [ 7 ]. A recent study found that stigma towards dementia is prevalent and deeply rooted in Taiwan general public and reported as the major barrier to seek diagnostic examinations and for caregivers to utilize services and ask for support [ 8 ].…”
Section: Introductionmentioning
confidence: 99%